Maternal prepregnancy overweight/obesity increase the risk of low Apgar scores in twins: a population-based cohort study in China - Feng, Zhoushan; Wu, Xiaohong; Tong, Xiaomei; He, Zheng; Yang, Chunxia; Shen, Wei; Ding, Yueqin; Liu, Jin; Meng, Qiong; Zhang, Aiqin; Jiang, Hong; Yan, Wenkang; et al. (Frontiers in Pediatrics, 2025)
ObjectiveWhile prepregnancy overweight or obesity is known to negatively impact maternal health, its effect on twin infants is not well understood. Therefore, we conducted a nationwide, multicenter retrospective study to investigate the association between maternal prepregnancy weight and health outcomes in twins.Study designThis study collected data from 22 healthcare units across 12 regions in China between January 2018 and December 2020. To control for confounding factors, multiple logistic regression, propensity score matching (PSM), inverse probability of treatment weighting (IPTW), and overlapping weighting models (OW) were applied to explore the effects of prepregnancy BMI on Apgar scores and other outcomes.ResultsAfter screening, a total of 4,724 women with twin pregnancies and 9,448 newborns were included in the study. Compared to normal prepregnancy weight, prepregnancy overweight/obesity significantly increased the risk of gestational hypertension and gestational diabetes in mothers [adjusted OR (95% CI): 1.85 (1.55–2.21) and 1.49 (1.27–1.74), respectively]. It also increased the incidence of twins with a 1-min Apgar score ≤7, whether they were larger or smaller [1.60 (1.20–2.13) and 1.45 (1.09–1.92), respectively]. Sensitivity analyses using PSM [1.60 (1.20–2.13) and 1.55 (1.07–2.25)], IPTW [1.67 (1.31–2.12) and 1.48 (1.17–1.87)], and OW [1.65 (1.08–2.57) and 1.47 (0.97–2.25)] confirmed the stability of these results. However, it did not affect the likelihood of a 5-min Apgar score ≤7 [adjusted OR (95% CI): 0.82 (0.24–2.17) and 1.40 (0.70–2.73)]. In contrast, prepregnancy underweight was associated with a reduced incidence of twins with a 1-min Apgar score ≤7 [adjusted OR (95% CI): 0.56 (0.32–0.92) and 0.58 (0.34–0.94)], but had no effect on the 5-min Apgar score ≤7 [adjusted OR (95% CI): 0.82 (0.24–2.17) and 0.22 (0.01–1.08)]. Prepregnancy BMI did not significantly affect twin birth weight discordance, NICU admission, preterm birth, or low birth weight.ConclusionMaternal overweight/obesity before pregnancy increases the risk of hypertensive disorders and gestational diabetes in twin pregnancies and significantly raises the likelihood of twins having a low 1-min Apgar score. However, no significant impact on 5-min Apgar scores was observed. These findings highlight the importance of managing weight before pregnancy and ensuring readiness for neonatal resuscitation during delivery.